Analisis Tingkat Pengetahuan Ibu terhadap Obat Diare Akut pada Pasien Anak di RS Umum Daerah Drs. Jocobus Luna,M.Si - Nadilla, Nadilla; Purwanti, Nera Umilia; Wahdaningsih, Sri (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Diarrhea is a collection of symptoms of infection that occurs in the human digestive tract caused by several organisms, namely bacteria, viruses and parasites. The aim of this study was to analyze the mother's level of knowledge and determine the influence of the mother's level of knowledge on acute diarrhea medicine in pediatric patients at the Drs Regional General Hospital. Jocobus Luna, M.Sc. The research method is prospective descriptive with a cross sectional research design. The tool used in the research was a questionnaire sheet and processed using SPSS. Sample selection used non-probability sampling techniques and a total of 100 respondents were obtained who met the inclusion criteria. The research results obtained were as many as 49 cases of child diarrhea, with the majority of mothers aged 26-35 years as much as 49%, having a history of education at high school level as much as 60% and 50% of mothers having jobs as housewives, and the highest level of mother's knowledge was in the sufficient group (40%). The conclusion of the research is that the P-Value value is 0.000, so there is an influence between the mother's level of knowledge and the incidence of diarrhea in children.